Willingness to pay for recreational attributes of public parks: A choice experiment approach - Hasan Basri, Bakti; Abd Karim, Mohd Zaini; Bakar, Normizan (World Scientific Publishing Company, 2015)
The choice to visit a park depends on individual preferences and understanding these preferences will be useful to parks' management decisions on facilities and infrastructure needs and maintenance.Choice experiment (CE) method is used to inform parks' management in Kuala Lumpur City, Malaysia on the social values of attributes available at the park.The latent class (LC) model is used to explore the effect of taste heterogeneity on the attributes.The results in the LC models indicate that the most preferred attribute at parks in Kuala Lumpur is recreational facilities. The willingness to pay (WTP) for these facilities range from RM3.25 to RM39.96.This shows that individuals can afford to pay up to RM40.00 per visit for such improvement in the attributes.